Hydrogen in the European power sector: A case study on the impacts of regulatory frameworks for green hydrogen - Julian Radek; Marco Sebastian Breder; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance (HEMF), 2024)
To ensure sustainable green hydrogen (H2) production, the European Union (EU) has introduced regulatory frameworks, such as the Delegated Act on Renewable Hydrogen. These regulations aim to ensure positive environmental effects through green hydrogen by establishing criteria of additionality, as well as spatial and temporal correlation. However, concerns have arisen among stakeholders regarding the potential barriers these criteria may pose to the growth of the EU hydrogen economy. Our analysis examines the implications of these regulations, analyzing the effects of the criteria on green hydrogen production from a system perspective. By doing that, we can assess the interplay with hydrogen production in European non-EU countries, as well as the role of third country import prices and quantities, while accounting for the EU objective of achieving net zero emissions by 2050. Our findings indicate that the EU hydrogen economy may be substantially affected by restrictive criteria for green hydrogen. Policy makers are therefore advised to carefully assess whether a level playing field can be established and to avoid overly restrictive unilateral measures.
Keywords: 330; Hydrogen economy; Green Hydrogen; Energy market modeling; Regulation